Comparative effectiveness among BRAF plus MEK inhibitors for patients with BRAF V600-mutant melanoma☆ - G.K. In; K. Chen; G. Sajeev; R. Simpson; S. Kalia; D. Christensen; D. Liu; N. Rezai; A. di Pietro; J. Signorovitch (ESMO Real World Data and Digital Oncology)
Background: Understanding of comparative efficacy of treatments can inform clinical decision-making. This study compared overall survival (OS) and progression-free survival (PFS) across patients with metastatic BRAFV600-mutant melanoma initiating encorafenib + binimetinib (ENCO + BINI), dabrafenib + trametinib (DAB + TRAM), and vemurafenib + cobimetinib (VEM + COBI). Materials and methods: In this hybrid study, we contextualized OS and PFS between patients with metastatic BRAF V600E/K-mutant melanoma receiving ENCO + BINI in the phase III COLUMBUS trial (enrollment: December 2013 to April 2015) versus real-world data (RWD) from a nationwide electronic health record-derived deidentified database (treatment initiation: 2014-2021). After observing consistent outcomes across trial and RWD, we compared OS and PFS for a pooled ENCO + BINI cohort across these settings versus comparable DAB + TRAM and VEM + COBI cohorts from the real-world database. Results: Of 716 patients [ENCO + BINI (n = 275; n = 192 from COLUMBUS, n = 83 from RWD), DAB + TRAM (n = 387), VEM + COBI (n = 54)], mean age was 56-60 years. OS and PFS were similar for ENCO + BINI-treated patients in COLUMBUS and RWD [adjusted hazard ratios: 1.03 (95% CI 0.62-1.72) for OS, 1.10 (0.69-1.75) for PFS]. Relative to the pooled ENCO + BINI group, adjusted OS and PFS were significantly worse for DAB + TRAM [OS: 1.32 (1.05-1.65), PFS: 1.49 (1.20-1.87)] and comparable for VEM + COBI [OS: 1.17 (0.76-1.79), PFS: 1.20 (0.79-1.82)]. Results were similar in comparisons based on the RWD groups alone, when trial data were excluded. Conclusions: OS and PFS were longer with ENCO + BINI relative to DAB + TRAM and comparable to VEM + COBI, after adjusting for differences in patient profiles. These findings add to evidence informing the use of combination v-Raf murine sarcoma viral oncogene homolog B protein (BRAF)/mitogen-activated protein kinase kinase (MEK) inhibitors in metastatic BRAF V600-mutant melanoma.